Social transformation in India : essays in honour of Professor I.P. Desai - Shah, Ghanshyam; Desai, Ishwarlal Pragji (Jaipur : Rawat Publications, 1997)
Festschrift in honor of Ishwarlal Pragji Desai, 1911-1985, sociologist; comprises contributed articles on social change in India.
Includes bibliographical references and index.
Keywords: Desai, Ishwarlal Pragji; Social reformers -- India -- Biography